The 4 per 1000 goal and soil carbon storage under agroforestry and conservation agriculture systems in sub-Saharan Africa. - CGIAR Research Program on Maize (2019)
peer reviewed journal article examining soil carbon storage under agroforestry and conservation agriculture systems